Trust is hard to come by: Disentangling the influence of structural characteristics and race on perceptions of trust in the police in a major Southern County. Issue 4 (2nd October 2017) - Burgason, Kyle A.
ABSTRACT: The current study will add to the literature on public attitudes toward law enforcement by assessing the individual and contextual-level predictors of one of the key concepts in police legitimacy literature: trust. Examining individuals nested within zip code results showed a significant equalizing effect of structural resource deprivation on both White and Black respondents' perceptions of trust in the police. Additionally, results found respondents who perceived racial profiling to be widespread had a universally decreased likelihood of having trust in the police, and these disparities were exacerbated as structural resource deprivation increased.